THE EFFECT OF BUDGET PLANNING AND BUDGET EVALUATION ON SOCIAL SERVICES PERFORMANCE OF KARAWANG DISTRICT - Sulistiyo, Hari; Pratiwi, Feren Ayu (Nominal: Barometer Riset Akuntansi dan Manajemen, 2021)
Abstract: The Effect of Budget Plannng and Budget Evaluation On Social Service performance of karawang District.The purpose of this study was to determine the effect of Budget Planning and Budget Evaluation on the Performance of the Social Service in Karawang Regency. Sampling in this study using of 150 respondents. The data collection technique uses a survey method with a questionnaire tool. Data analysis was performed by validity test, reliability test, descriptive analysis and verification analysis with multiple linear regression. The results of this study show that simultaneously with statistical tests it shows that budget planning and budget evaluation have a significant effect on the performance of the Social Service of Karawang Regency. In addition, partially budget planning has a significant effect on the performance of the Social Service of Karawang Regency, budget evaluation has a significant effect on the performance of the Karawang Regency Social Service.Keywords: Budget Planning, Budget Evaluation, PerformanceAbstrak: Pengaruh Perencanaan Anggaran dan Evaluasi Anggaran Terhadap Kinerja Dinas Sosial Kabupaten Karawang.Tujuan penelitian ini adalah untuk mengetahui pengaruh Perencanaan Anggaran dan Evaluasi Anggaran terhadap Kinerja Dinas Sosial Kabupaten Karawang. Pengambilan sampel dalam penelitian ini menggunakan sampel sebanyak 150 responden. Teknik pengumpulan data menggunakan metode survei dengan alat angket. Analisis data dilakukan dengan uji validitas, uji reliabilitas, analisis deskriptif dan analisis verifikatif dengan regresi linier berganda. Pengolahan data menggunakan aplikasi software SPSS Versi 20. Hasil penelitian ini menunjukkan bahwa secara simultan dengan uji statistik menunjukkan bahwa perencanaan anggaran dan evaluasi anggaran berpengaruh signifikan terhadap kinerja Dinas Sosial Kabupaten Karawang. Selain itu, secara parsial perencanaan anggaran berpengaruh signifikan terhadap kinerja Dinas Sosial Kabupaten Karawang, evaluasi anggaran berpengaruh signifikan terhadap kinerja Dinas Sosial Kabupaten Karawang.Kata Kunci: Perencanaan Anggaran, Evaluasi Anggaran, Kinerja